2017
DOI: 10.1007/s40093-017-0169-3
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inorganic fertilizer application enhances the effect of Bradyrhizobium on nodulation and yield of peanut (Arachis hypogea L.) in nutrient depleted and sandy soils of Ethiopia

Abstract: Purpose An investigation was carried out to evaluate the effect of the integrated application of organic and inorganic fertilizer effect on Bradyrhizobium effectiveness on nodulation and yield of peanut at the major growing areas of Eastern Ethiopia, Babillae and Fedis sites. Methods Systemic combination of compost, manure, Bradyrhizobium inoculation and NP application was laid out in Randomized Complete Block Design with three replications. Results The result showed that Bradyrhizobium integrated with organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
8
0
3
Order By: Relevance
“…Similarly, it has been shown that residual soil N increased significantly with the application of DAP fertilizer i.e. 46 kg P 2 O 5 ha −1 combined with 18 kg N ha −1 at Babile site in Ethiopia ( Argaw, 2017 ). Chalk (1991) indicated that when N fixing crops are included in crop rotation system, the plant can satisfy all or at least part of its N requirements through BNF and the amount of fixed N in excess of the current plants requirement will be stored in the soil and benefit subsequent corps.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, it has been shown that residual soil N increased significantly with the application of DAP fertilizer i.e. 46 kg P 2 O 5 ha −1 combined with 18 kg N ha −1 at Babile site in Ethiopia ( Argaw, 2017 ). Chalk (1991) indicated that when N fixing crops are included in crop rotation system, the plant can satisfy all or at least part of its N requirements through BNF and the amount of fixed N in excess of the current plants requirement will be stored in the soil and benefit subsequent corps.…”
Section: Resultsmentioning
confidence: 92%
“…strains combined with phosphorus fertilizer induced the best nitrogen accumulation rates in different groundnut parts (Didagbé et al 2014). Similarly, Argaw (2017) found that the highest total biomass yield, kernel yield and plant N accumulation of peanut were found where Bradyrhizobium in conjunction with organic fertilizer was applied. This shows the importance of organic fertilizer application in increasing yield of peanut.…”
Section: Nitrogen Uptake (Kg Ha -1 )mentioning
confidence: 87%
“…El ES también permitió identificar los excedentes orgánicos como el estiércol del ganado, las vainas de cacao y otros elementos vegetales que pueden ser aprovechados por los campesinos de la región en la elaboración de vermicompost, el cual es rico en microorganismos (Asadu y col., 2019;Barbero y Toso, 2006;FAO, 2013). Esto es beneficioso para los cultivos, debido a que contiene grandes cantidades de bacterias fijadoras de nitrógeno que mejora la retención de agua, la salud biológica y la capacidad de absorción del suelo, el aprovechamiento de las aguas pluviales, la actividad enzimática, la presencia de nutrientes, entre otros (Agegnehu y col., 2016;Argaw, 2017;Rayen y col., 2006;Sharma y col., 2017;Wang y col., 2016); lo que podría convertirse en una oportunidad para solucionar los problemas identificados en materia de contaminación y para apoyar el desarrollo de la agricultura responsable y sostenible.…”
Section: El Es Para El Análisis De Upasunclassified